The Dialogue on Papuan-ness and Indonesian-ness in History Learning In Senior High School - Susanto T. Handoko (Metafora: Education, Social Sciences and Humanities Journal, 2023)
ABSTRACT The results of several studies by both Indonesian and foreign researchers indicate that there is a decline in the sense of nationalism in Indonesia and there is still a real threat of a separatist movement wanting to separate themselves from Indonesia. To overcome this problem, schools as the vanguard of education must be able to become agents of nationalism guards through the historical education process. This study aims to develop Papuan-ness and Indonesian-ness dialogue in learning history at senior high school in Jayapura City. The research was conducted with a qualitative method and data collection techniques were carried out by observation, in-depth interviews and documentation. Data analysis using the Miles and Huberman Model interactive technique includes: data collection, data reduction, data presentation, and verification. The sources (types) of data in this study come from phenomena (events), informants, and documents. The results of this study show that history education plays an important role in strengthening Indonesian identity among students by promoting Papuan-ness and Indonesian-ness dialogue. Keywords: Dialogue, Papuaan-ness, Indonesiaan-ness, History Learning, Senior High School